Microfluidic System for Vitrification of Oocytes - Zhang Yuqi; Yu Zixuan; Zhou Xinli (Zhileng xuebao)
The demand for oocyte vitrification has increased. However, the current step-by-step loading and removal of cryoprotectants by manual or automatic storage devices may cause osmotic injury and the loss of cells. In this study, low-cost polymethyl methacrylate (PMMA) microfluidic chips and quartz capillaries were used to build a microfluidic system that achieved not only the continuous loading and removal of cryoprotectants but also the subsequent immersion in liquid nitrogen to realize automatic vitrification. MII mouse oocytes were loaded or unloaded with cryoprotectants by manual multistep and microfluidic methods, and the cell volume changes, survival, and oocyte development rates were compared. The results demonstrate that the survival, cleavage, and blastocyst rates of oocytes were 93. 25%, 77. 12%, and 53. 00%, respectively, for the 8 min loading / unloading duration group. These are significantly higher than those of the manual multistep group but not significantly different from those of the control group (P <0. 05). In conclusion, the microfluidic system using the PMMA chip and quartz capillaries significantly reduced osmotic injury and cell loss, and simplified the operational steps. This system may provide key technical support for the development of automated devices for oocyte and embryo vitrification based on microfluidic technology.